A heat-resistant Bi / Mg oxide for high-temperature iodine capture and its preparation method and use
By preparing Bi/Mg oxide, the problem of low thermal stability of iodine capture materials at high temperatures in the prior art is solved, and high iodine capture performance at temperatures higher than the iodine boiling point is achieved.
Patent Information
- Application Number
- CN202410837212.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-26
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-06-26
AI Technical Summary
The prior art materials that capture volatile iodine at high temperatures have low thermal stability and lack the ability to capture at temperatures higher than the boiling point of the iodine.
By using the preparation method of Bi/Mg oxide, bismuth salt and magnesium salt are mixed in water, citric acid and ethylene glycol are added, and hydrothermal reaction is carried out to obtain Bi/Mg oxide with high thermal stability.
The material has a high iodine capture performance of 367.72-528.87 mg/g after 10 hours at 200°C. The iodine capture capacity reaches 584.8 mg/g after 26 hours at 200°C, which significantly improves the thermal stability and iodine capture capacity at high temperatures.
Smart Images

Figure CN118663211B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorption material preparation, and in particular relates to a heat-resistant Bi / Mg oxide for high-temperature iodine capture, and a preparation method and application thereof. Background Art
[0002] Nuclear fuel reprocessing plants release large amounts of volatile radioactive iodine, including various isotopes such as 129 I. 131 I. 132 I and 133 I. These isotopes have different decay rates, e.g. 131 I half-life is 8.04 days, 129 The half-life of I is 1.57×10 7Years, after exposure to the human living environment, will cause serious damage to human health and have direct or long-term effects. In view of the increasing demand for uranium resources required for clean nuclear energy production, nuclear plants choose to recycle spent nuclear fuel to obtain uranium-235 resources. Nuclear reactor accidents are also another challenge facing the nuclear industry. Both nuclear fuel recycling and nuclear accidents release radioactive nuclides at high temperatures. These radioactive nuclides, especially iodine isotopes, must be captured before they interact with the air to reduce contamination. One of the methods to capture volatile iodine under high temperature conditions is to use thermally stable adsorbents. Several materials from the porous inorganic family have been used for radioiodine capture, such as: B. Azambre, M. Chebbi, O. Leroy, L. Cantrel, Effects of zeolite parameters and irradiation on the retention properties of silver zeolites exposed to molecular iodine, Ind. Eng. Chem. Res. 57 (2018) 1468–1479. https: / / doi.org / 10.1021 / acs.iecr.7b03579; Y. Nan, L. L. Tavlarides, D. W. Depaoli, Adsorption of iodine onto hydrogen-reduced silver-exchanged mercerized salts: Experiments and modeling, American Institute of Chemical Engineering 63 (2016) 1024–1035. https: / / doi.org / 10.1002 / aic. However, many of these materials have low thermal stability when adsorption is performed at high temperatures. Although porous inorganic materials generally exhibit lower iodine capture performance than porous organics, metal oxides have many favorable properties that can be used to develop thermally stable adsorbents with high iodine capture capacity and cost-effectiveness. Despite these advantages of metal oxides in iodine capture, convincing metal oxides for iodine capture at temperatures above the boiling point of iodine (180°C) still need to be improved. Therefore, it is urgent to find modification methods to create improved structures of mixed metal oxides with metal ions of different valences (divalent and trivalent) that can remain stable at high temperatures while capturing large amounts of iodine in their boiling state without significantly changing the adsorbent. Summary of the invention
[0003] The first object of the present invention is to provide a heat-resistant Bi / Mg oxide and a preparation method thereof. The Bi / Mg mixed oxide prepared by the method has excellent high thermal stability, so that iodine can be captured at a temperature higher than the boiling point of iodine (184° C.), thereby solving the problem of low thermal stability in the prior art.
[0004] The second object of the present invention is to provide a practical application of the above material for capturing iodine at high temperature. The present invention solves the problem of low iodine capture capacity at high temperature of 100-200°C and the problem of easy desorption of iodine captured at high temperature of 80-100°C in the prior art.
[0005] The purpose of the present invention is achieved through the following technical solutions:
[0006] A method for preparing a heat-resistant Bi / Mg oxide comprises the following steps:
[0007] Dissolve bismuth salt and magnesium salt in water and mix them evenly to obtain a mixed solution A; add citric acid to the mixed solution A under stirring, add ethylene glycol, and mix evenly to obtain a mixed solution B; heat the mixed solution B at 70-80°C
[0008] The mixture is preheated by stirring at 400 °C, and then a hydrothermal reaction is carried out at 120-140 °C; the product obtained by the reaction is centrifuged, washed with deionized water, dried, and calcined to obtain Bi / Mg oxide.
[0009] Preferably, define X = [Bi 3+ ] / [Mg 2+ ], in the mixed solution A: 0.5≤X≤2.
[0010] More preferably, X=0.5.
[0011] Preferably, the magnesium salt is a water-soluble magnesium salt, such as Mg(NO3)2·6H2O or MgCl2·6H2O; the bismuth salt is a water-soluble bismuth salt, such as Bi(NO3)3·5H2O or BiCl3·5H2O.
[0012] The citric acid is a reducing agent in the above reaction.
[0013] Preferably, the ratio of the total molar amount of the bismuth salt and the magnesium salt to the molar amount of citric acid is 1:2.
[0014] Preferably, the ethylene glycol is added 10 minutes after the addition of the citric acid.
[0015] The ethylene glycol is a cross-linking agent. Preferably, the volume ratio of the mixed solution A to the ethylene glycol is (20-30):1.
[0016] Preferably, after adding ethylene glycol, ultrasonic treatment is performed for 10 to 30 minutes to ensure uniform mixing.
[0017] After the ultrasonic treatment, the mixture B is preferably preheated in an oil bath at 70-80°C for 20-30 minutes, and then subjected to a hydrothermal reaction treatment at 120-140°C.
[0018] Preferably, the hydrothermal reaction time is 7 to 10 hours.
[0019] After centrifugal washing, the drying is preferably performed at 60 to 80° C. for 24 to 48 hours.
[0020] Preferably, the Bi / Mg oxide is obtained by calcining at 300-550° C. for 1-2 hours.
[0021] More preferably, the Bi / Mg oxide is obtained by calcining at 500°C.
[0022] Further preferably, during the calcination, the heating rate from room temperature to the calcination temperature is 5-10° C. / min.
[0023] The present invention also provides Bi / Mg oxide prepared by the above method.
[0024] The present invention also provides application of Bi / Mg oxide prepared by the method in high-temperature iodine capture.
[0025] Preferably, the mass ratio of Bi / Mg oxide to iodine is (0.3-0.5):(3-6).
[0026] Preferably, the adsorption temperature is 184° C. to 200° C., and the iodine capture time is 1 hour to 26 hours. The adsorption temperature meets the temperature conditions of a nuclear fuel reprocessing plant and the temperature conditions that can be met when a nuclear reactor leaks.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The mixed metal oxide prepared by the present invention improves the thermal stability at high temperature (600-800° C.), and this heat resistance enables the Bi / Mg oxide material to have a high iodine capture performance of 367.72-528.87 mg / g after 10 hours at 200° C., and the iodine capture capacity reaches 584.8 mg / g after 26 hours at 200° C. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the XRD spectrum of the Bi / Mg oxide of Example 1.
[0030] Figure 2 The XRD pattern of Bi / Mg oxide prepared at 500°C in Example 1-3.
[0031] Figure 3 XRD patterns of Bi / Mg oxide (1:2) before iodine capture and its iodine-loaded counterpart I2@Bi / Mg oxide (1:2) prepared at 500°C in Example 1.
[0032] Figure 4 This is a SEM micrograph of the Bi / Mg oxide (1:2) prepared in Example 1.
[0033] Figure 5 This is a SEM micrograph of I2@Bi / Mg oxide (1:2) obtained after Bi / Mg oxide captured iodine in Example 1.
[0034] Figure 6These are the XPS results of Bi / Mg oxide (1:2) and I2@Bi / Mg oxide (1:2) of Example 1.
[0035] Figure 7 This is the TGA result diagram of Bi / Mg oxide (1:2) and I2@Bi / Mg oxide (1:2) prepared in Example 1.
[0036] Figure 8 The effect of time on iodine adsorption of Bi / Mg oxide (1:2) prepared in Example 1 and the pseudo-first-order and pseudo-second-order kinetic models.
[0037] Fig. 9 This is a graph of the iodine capture performance of the materials prepared at different calcination temperatures in Example 1.
[0038] Fig.10 Graph showing the iodine capture performance of Bi / Mg oxides with different Bi / Mg molar ratios in Examples 1-3.
[0039] Fig.11 This is the result of iodine desorption from Bi / Mg oxide (1:2) at 100°C.
[0040] Fig.12 : This is the nitrogen adsorption / desorption isotherm of the Bi / Mg oxide (1:2) in Example 1 at 77K.
[0041] Fig.13 The porosity of the Bi / Mg oxide (1:2) prepared in Example 1. DETAILED DESCRIPTION
[0042] The present invention will be further described below in conjunction with specific embodiments, and the advantages and features of the present invention will become clearer as the description proceeds. However, the embodiments are exemplary only and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the scope of protection of the present invention.
[0043] Example 1
[0044] A Bi / Mg oxide (X=0.5) and a preparation method thereof, the method comprising the following steps:
[0045] Bi(NO3)3·5H2O (7.27 g, 0.015 mol) and Mg(NO3)2·6H2O (7.68 g, 0.03 mol) were dissolved in 300 mL of deionized water at a molar ratio of 1:2, and a mixed solution A was obtained under magnetic stirring at room temperature. Citric acid (C6H8O7) was used as a fuel and added to the mixed solution A. 17.29 g (0.09 mol) of citric acid was added to the mixed solution A containing 300 mL of deionized water, and the molar ratio of the above two metal nitrates to citric acid was 1:2. Ten minutes after the addition of citric acid, 10 mL of ethylene glycol (EG) was added as a cross-linking agent to obtain a mixed solution B with a total volume of 310 mL. The obtained mixed solution B was then placed in an oil bath at 80°C and stirred continuously until a uniform mixture was formed, and then transferred to a polytetrafluoroethylene-lined autoclave and hydrothermally treated at 140°C for 10 hours. The resulting mixture was then cooled to room temperature, centrifuged several times after adding water, dried under vacuum at 80 °C, and finally calcined in a muffle furnace at different temperatures (300 °C, 500 °C, 550 °C) at a heating rate of 10 °C / min for 2 h to form three mixed metal oxides (1:2).
[0046] The above three mixed metal oxides were subjected to iodine capture at 200°C for 10 hours to optimize the best calcination temperature. The absorbance of Bi / Mg oxide (1:2) calcined at 300°C was 231.72 mg / g, the absorbance of Bi / Mg oxide (1:2) calcined at 500°C was 528.87 mg / g, and the absorbance of Bi / Mg oxide (1:2) calcined at 550°C was 479.83 mg / g. The optimal calcination temperature was 500°C, and this condition was used for the following other experiments.
[0047] The Bi / Mg oxide (1:2) obtained by calcining at 500°C was subjected to iodine capture at 200°C for 26 hours. 127 I particles were placed in a small glass container. The glass container was covered with a glass funnel with a microporous disk in the center, 0.5 g of Bi / Mg oxide (1:2) was evenly dispersed on it, and then placed in a Teflon-lined stainless steel autoclave and sealed, and finally placed in an oven at 200°C.
[0048] The iodine uptake capacity (Q, mg / g) of the Bi / Mg oxide material prepared above was evaluated by weight measurement of the sample before and after iodine capture under static conditions. The iodine capacity of the Bi / Mg oxide (1:2) calcined at 500°C to capture iodine for 26 hours at 200°C was 584.8 mg / g.
[0049] The desorption experiment was carried out by heating the iodine-loaded sample. In practice, 1.46 g of I2@(Bi / Mg oxide, 1:2) was placed in an unsealed glass vial and heated in an oven at 100°C for 2, 6 and 10 h. The chemically adsorbed iodine capacity was calculated based on the final mass after heating, and the physically adsorbed iodine capacity was calculated by subtracting the chemically adsorbed iodine capacity from the total iodine capture capacity at 10 h. The iodine capacity (mg / g) of the material prepared in Example 1 was evaluated by the weight method of the sample before and after iodine capture under static conditions. The iodine capacity of the Bi / Mg oxide (1:2) calcined at 500°C for 26 h at 200°C was 584.8 mg / g.
[0050] The results showed that the chemical adsorption amount was 511.31 mg / g and the physical adsorption amount was 17.55 mg / g, which were 96.68% and 3.32%, respectively. These results indicate that the capture process of iodine is a chemical process rather than a physical process, which is consistent with the results of kinetic studies, indicating that the pseudo-secondary process is dominant.
[0051] The thermal stability of Bi / Mg Oxide and its iodine-loaded product I2@Bi / Mg Oxide in the range of room temperature to 600°C was studied by thermogravimetric analysis (TGA). The total weight loss of Bi / Mg oxide was 0.37%. The total weight loss of I2@Bi / Mg oxide was 0.74%.
[0052] Iodine capture was performed with 0.5 g Bi / Mg oxide and 3 g iodine pellets at 200°C for different times from 1 h to 26 h in a sealed heat-resistant glass. The iodine capture capacity Q (Mg / g) was evaluated gravimetrically. The iodine capture capacity of Bi / Mg oxide at 200°C was 528.87 mg / g after 10 h of the experiment and 584.8 mg / g after 26 h of the experiment.
[0053] Example 2
[0054] A Bi / Mg oxide (X=1) and a preparation method thereof, the method comprising the following steps:
[0055] Bi(NO3)3·5H2O (7.27 g, 0.015 mol) and Mg(NO3)2·6H2O (3.84 g, 0.015 mol) were dissolved in 300 mL of deionized water at a molar ratio of 1:1, and a mixed solution A was obtained under magnetic stirring at room temperature. Citric acid (C6H8O7) was used as a fuel and added to the mixed solution A. 11.52 g (0.06 mol) of citric acid was added to the mixed solution A containing 300 mL of deionized water, and the molar ratio of the above two metal nitrates to citric acid was 1:2. Ten minutes after the addition of citric acid, 10 mL of ethylene glycol (EG) was added as a crosslinking agent to obtain a mixed solution B with a total volume of 310 mL. The obtained mixed solution B was then placed in an oil bath at 80°C and stirred continuously until a uniform mixture was formed, and then transferred to a polytetrafluoroethylene-lined autoclave and hydrothermally treated at 140°C for 10 hours. The resulting mixture was then cooled to room temperature, centrifuged several times after adding water, dried at 80 °C in vacuum, and finally calcined at 500 °C for 2 h in a muffle furnace at a heating rate of 10 °C / min to obtain Bi / Mg metal oxide (1:1).
[0056] The obtained conditions were optimized according to Example 1, and the Bi / Mg oxide was calcined at 500°C and iodine was captured at 200°C for 26h. 127 I particles and put them into a small glass container. Cover the glass container with a glass funnel with a microporous disk in the middle, 0.5g Bi / Mg oxide (1:1) is evenly dispersed on the funnel, then put it into a Teflon-lined stainless steel autoclave, seal it, and finally put it into an oven at 200℃.
[0057] Under static conditions, the iodine absorption (Q, mg / g) of the sample before and after Bi / Mg oxide (1:1) captured iodine was measured by gravimetric method. The iodine capture capacity of Bi / Mg oxide (1:1) at 200℃ for 10h was 407.13 mg / g.
[0058] Example 3
[0059] A Bi / Mg oxide (X=1.5) and a preparation method thereof, the method comprising the following steps:
[0060] Bi(NO3)3·5H2O (7.27 g, 0.015 mol) and Mg(NO3)2·6H2O (2.56 g, 0.01 mol) were dissolved in 300 mL of deionized water at a molar ratio of 1.5:1, and a mixed solution A was obtained under magnetic stirring at room temperature. Citric acid (C6H8O7) was used as a fuel and added to the mixed solution A. 9.60 g (0.05 mol) of citric acid was added to the mixed solution A containing 300 mL of deionized water, and the molar ratio of the above two metal nitrates to citric acid was 1:2. Ten minutes after the addition of citric acid, 10 mL of ethylene glycol (EG) was added as a crosslinking agent to obtain a mixed solution B with a total volume of 310 mL. The obtained mixed solution B was then placed in an oil bath at 80°C and stirred continuously until a uniform mixture was formed, and then transferred to a polytetrafluoroethylene-lined autoclave and hydrothermally treated at 140°C for 10 hours. The resulting mixture was then cooled to room temperature, centrifuged several times after adding water, dried at 80 °C in vacuum, and finally calcined at 500 °C for 2 h in a muffle furnace at a heating rate of 10 °C / min to obtain Bi / Mg metal oxide (1.5:1).
[0061] According to Example 1, Bi / Mg oxide was calcined at 500°C and iodine was captured at 200°C for 26 hours. 127 I particles and put them into a small glass container. Cover the glass container with a glass funnel with a microporous disk in the middle, 0.5g Bi / Mg oxide (1.5:1) is evenly dispersed on the funnel, then put it into a Teflon-lined stainless steel autoclave, seal it, and finally put it into an oven at 200℃.
[0062] The iodine uptake (Q, mg / g) of Bi / Mg oxide (1.5:1) was determined gravimetrically under static conditions. The iodine capture capacity of Bi / Mg oxide (1.5:1) at 200°C for 10 h was 367.72 mg / g.
[0063] Figure 1 is the XRD analysis of the Bi / Mg oxide (1:2) prepared in Example 1, showing the comparison of the XRD diffractions of the metal oxides calcined at 300°C, 500°C and 550°C. Figure 1 It shows that the crystallinity increases with the increase of calcination temperature. The material calcined at 500℃ has the highest crystallinity and better iodine capture, so it can be used for other experiments. Figure 1 It can be seen that the Bi / Mg oxide (1:2) calcined at 500 °C has a two-phase structure with an alkali-centered cubic structure and a symmetry of the I23 (197) space group. XRD analysis reveals that Bi 18 Mg8O 36 Hybrid phase with ICDD PDF#36-0914 and Bi 12MgO 19 The formation of a hybrid phase of (γ-Bi2O3) and ICDDPDF#42-0182. The above two phases are similar and adopt a base-centered cubic structure with a unit cell parameter of Bi 18 Mg8O 36 and Bi 12 MgO 19 The (γ-Bi2O3) phase is characterized by the presence of magnesium ion vacancies that create porosity defects within both phases, allowing iodine atoms to easily penetrate into the material matrix. The magnesium vacancies make the structure rich in oxygen atoms and produce bismuth polyhedra, which allow the capture of iodine through strong oxygen-iodine bonds. The material calcined at 500°C shows an XRD pattern with the strongest peak basal spacing of Calcination of the material at temperatures above 500 °C resulted in a decrease in the XRD peak intensity, indicating that the material changed its structural integrity at 550 °C.
[0064] Figure 2 A comparison of the XRD diffraction peaks of the Bi / Mg oxides calcined at different molar ratios at an optimized temperature (500° C.) prepared in Example 1, Example 2, and Example 3 is shown. The crystallinity of all materials is similar regardless of their Bi / Mg molar ratios, since the XRD diffraction is mainly due to the presence of Bi2O3, which is the main phase in the Bi / Mg mixed oxides.
[0065] Figure 3 A comparison of the XRD patterns of Bi / Mg oxide (1:2) calcined at 500°C and its iodine loaded counterpart is shown. The XRD patterns indicate the formation of new XRD peaks upon iodine capture, corresponding to the formation of BiI3, BiOI, and Bi5O7I phases.
[0066] Figure 4 and Figure 5 SEM of the material prepared in Example 1. The micrograph of Bi / Mg oxide (1:2) shows that the adsorbent has small bends and helical rods with holes, which may be caused by defects in oxygen atoms within the crystal. After iodine adsorption, the size of the bends and helical rods increases, confirming the adsorption of iodine.
[0067] Figure 6 An XPS total scan is shown, showing all elements present in the Bi / Mg oxide (1:2) and comparing the adsorbed material before and after iodine capture. The XPS total scan after iodine capture shows a pair of clear iodine peaks, which confirms the presence of iodine in the sample after adsorption.
[0068] Figure 7 The thermal stability of the material prepared in Example 1 is shown. Figure 7The thermal stability in Example 2 and Example 3 is also explained. It can be seen that Bi / Mg oxide (1:2) is very stable with a total weight loss of only 0.37%. In the early stages of the TGA curve, a buoyancy effect is observed, indicating the weight nature of the material. Only a total weight loss of 0.74% is observed after iodine capture. This indicates that the stability of the material is high after iodine capture, and the iodine is mainly chemically absorbed.
[0069] Figure 8 The experimental adsorption data as well as the nonlinear pseudo-first-order and pseudo-second-order models are shown. The figure shows that the pseudo-second-order fits the adsorption data better, confirming that the adsorbed iodine is mostly chemisorbed.
[0070] Fig. 9 The figure shows the comparison of the iodine capture capacity of the Bi / Mg oxide (1:2) prepared in Example 1 calcined at different temperatures (300°C, 500°C and 550°C). The Bi / Mg oxide (1:2) calcined at 500°C showed the highest iodine capacity of 528.87 mg / g after adsorption at 200°C for 10 hours.
[0071] Fig.10 The iodine capture capabilities of the Bi / Mg oxides prepared in Example 1, Example 2 and Example 3 were compared, with molar ratios of X = 0.5, X = 1 and X = 1.5, respectively. The material with a molar ratio of X = 0.5, i.e., magnesium oxide (1:2), showed the best iodine capture performance and was therefore used for all other experiments.
[0072] Fig.11 The desorption of iodine by Bi / Mg oxide (1:2) prepared in Example 1 is shown. Desorption experiments were performed on samples with different iodine contents and different adsorption times. The iodine desorption of all samples showed that the chemical absorption capacity was much greater than the physical absorption capacity.
[0073] Fig.12 The nitrogen adsorption / desorption isotherms of the Bi / Mg oxide (1:2) prepared in Example 1 at 77 K are shown, wherein the BET surface area is 80.6 m 2 / g. Bi / Mg oxide (1:2) exhibits a type II isotherm with H3-type hysteresis at high relative pressure (P / Po>0), indicating that the monolayer-multilayer adsorption of N2 is not limited.
[0074] Fig.13 The porosity of the Bi / Mg oxide (1:2) prepared in Example 1 is shown in FIG. 1 , wherein the pore volume of the Bi / Mg oxide (1:2) is 0.18 cm 3 / g.
[0075] Compared with other existing materials listed in the background of the present invention, the Bi / Mg oxide of the present invention captures iodine mainly through a chemical absorption process of iodine bonding with two oxygens of bismuth polyhedrons, while other existing materials capture iodine mainly through a physical adsorption process.
[0076] In the prior art, a Chinese patent entitled 2-mercaptobenzimidazole functionalized Bi / Mg oxide, preparation method and application thereof (application number 2024012602059860) also provides an adsorbent of Bi / Mg oxide (X=0.42), but compared with the present invention, it has the following differences:
[0077] (1) The above prior art uses NaOH as a precipitant and is prepared by a precipitation method. However, the Bi / Mg oxide prepared in the present invention is prepared by igniting Bi(NO3)3·5H2O and Mg(NO3)2·6H2O salts using citric acid as a fuel.
[0078] (2) The Bi / Mg oxide (X=0.42) prepared in the prior art shows an XRD peak pattern different from that of the present invention. In the prior art, the d-substrate spacing of the strongest XRD peak is In the present invention, the d-substrate spacing of the strongest XRD peak of Bi / Mg oxide (1:2) is Therefore, the composition of the oxidized Bi / Mg phase (X=0.42) of the prior art is substantially different from that of the present invention.
[0079] (3) Although the above prior art does not disclose the porosity of Bi / Mg oxide (X=0.42), the material prepared by the coprecipitation method is generally referred to as a non-porous material. Compared with the material prepared by the citric acid-promoted combustion reaction of the present invention, the different preparation methods obviously lead to materials with different structures and porosities.
[0080] (4) The above prior art discloses an iodine capture process, wherein the iodine capture is completed at 150°C, which is lower than the boiling point of iodine (184°C). The present invention discloses that the Bi / Mg oxide material has a high iodine capture performance of 367.72-528.87 mg / g after 10 hours at 200°C (higher than the boiling point of iodine), and the iodine capture capacity reaches 584.8 mg / g after 26 hours at 200°C. Moreover, the above prior art does not disclose the specific surface area and parameters of the material required for the large-scale application of Bi / Mg oxide (X=0.42) for iodine capture at a temperature particularly higher than the boiling point of iodine.
Claims
1. A method for preparing a heat-resistant Bi / Mg oxide for high-temperature iodine capture, characterized in that: The following steps are involved: Dissolve bismuth salt and magnesium salt in water and mix them evenly to obtain a mixed solution A; add citric acid to the mixed solution A under stirring, then add ethylene glycol, and mix evenly to obtain a mixed solution B; stir and preheat the mixed solution B at 70-80° C., and then perform a hydrothermal reaction at 120-140° C.; centrifuge the product obtained by the reaction, wash with deionized water, dry, and calcine to obtain Bi / Mg oxide; The ratio of the total molar amount of the bismuth salt and the magnesium salt to the molar amount of citric acid is 1:
2.
2. The method for preparing a heat-resistant Bi / Mg oxide for high-temperature iodine capture according to claim 1, characterized in that: Define X = [Bi 3+ ] / [Mg 2+ ], X is the molar ratio, in the mixed solution A: 0.5≤X≤2.
3. The method for preparing a heat-resistant Bi / Mg oxide for high-temperature iodine capture according to claim 2, characterized in that: Said X=0.
5.
4. The method for preparing a heat-resistant Bi / Mg oxide for high-temperature iodine capture according to claim 1, characterized in that: The magnesium salt is Mg(NO3)2·6H2O or MgCl2·6H2O; the bismuth salt is Bi(NO3)3·5H2O or BiCl3·5H2O.
5. The method for preparing a heat-resistant Bi / Mg oxide for high-temperature iodine capture according to claim 1, characterized in that: The ethylene glycol was added 10 minutes after the addition of the citric acid.
6. The method for preparing a heat-resistant Bi / Mg oxide for high-temperature iodine capture according to claim 1, characterized in that: The volume ratio of the mixed liquid A to ethylene glycol is (20-30):
1.
7. The method for preparing a heat-resistant Bi / Mg oxide for high-temperature iodine capture according to claim 1, characterized in that: After adding ethylene glycol, ultrasonic treatment was performed for 10 to 30 minutes.
8. The method for preparing a heat-resistant Bi / Mg oxide for high-temperature iodine capture according to claim 1, characterized in that: The mixture B was preheated in an oil bath at 70-80°C for 20-30 minutes, and then subjected to a hydrothermal reaction at 120-140°C.
9. The method for preparing a heat-resistant Bi / Mg oxide for high-temperature iodine capture according to claim 1, characterized in that: The hydrothermal reaction time is 7 to 10 hours.
10. The method for preparing a heat-resistant Bi / Mg oxide for high-temperature iodine capture according to claim 1, characterized in that: The drying is performed at 60 to 80° C. for 24 to 48 hours.
11. The method for preparing a heat-resistant Bi / Mg oxide for high-temperature iodine capture according to claim 1, characterized in that: The calcination is carried out at 300-550° C. for 1-2 hours.
12. The method for preparing a heat-resistant Bi / Mg oxide for high-temperature iodine capture according to claim 11, characterized in that: The calcination was performed at 500°C.
13. The method for preparing a heat-resistant Bi / Mg oxide for high-temperature iodine capture according to claim 1, characterized in that: In the calcination, the heating rate from room temperature to the calcination temperature is 5-10°C / min.
14. Bi / Mg oxide obtained by the preparation method according to any one of claims 1 to 13.
15. Use of the Bi / Mg oxide according to claim 14 in high temperature iodine capture.
Citation Information
Patent Citations
2-mercaptobenzimidazole functionalized Bi / Mg oxide and preparation method and application thereof
CN117942923A